Clinical Manifestation and Management of Extra-Esophageal Gastroesophageal Reflux Disease - Juwanto Juwanto; Chudahman Manan (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2002)
GERD is a condition that gastric content go back into the esophagus. This condition could came disturbances in the respiratory tract, heart and otolaryng. Those extra-esophageal clinical manifestation are common but often miss our attention. So it is important to explorate it further. The management of extra-esophageal GERD is similar with management of GERD. It is included life style modification and reducing refluxate with controlling pH with aggressiveness.    Keywords: extra gerd, non cardiac chest pain, respiratory disturbance, omeprazole